Association of Heart Rate with N-Terminal Pro-B-Type Natriuretic Peptide in Septic Patients: A Prospective Observational Cohort Study. Issue 6 (December 2016) - Hayase, Naoki; Yamamoto, Miyuki; Asada, Toshifumi; Isshiki, Rei; Yahagi, Naoki; Doi, Kent
Abstract : ABSTRACT: Background: Excessive sympathetic stress has multiple adverse effects during critical illness including sepsis. Recent studies showed that heart rate control had a significant effect on reducing mortality in septic shock patients. Furthermore, elevated N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels in septic patients were reportedly associated with adverse outcome. However, no study has evaluated the relationship between hemodynamic profiles of septic patients and the circulating cardiac biomarker. Our objective was to determine whether hemodynamic profiles, specifically tachycardia and new-onset atrial fibrillation (AF), were associated with NT-proBNP elevation in septic patients. Methods: We consecutively enrolled patients admitted to our intensive care unit (ICU). NT-proBNP levels, heart rate, and rhythm at ICU admission were measured, and all clinical and laboratory data were prospectively collected. Tachycardia was defined as a heart rate of above 100 bpm. Results: Ninety-five patients out of 267 patients (35.6%) were diagnosed as sepsis. Of these septic patients, 47 presented with tachycardia and 6 developed new-onset AF. Multivariate Cox regression analysis revealed that tachycardia was an independent predictor of 28-day overall survival in septic patients (hazard ratio, 4.22; 95% confidence interval, 1.10–27.72; P  < 0.05), but not in nonseptic patients. Multivariate linear regression analysis demonstrated that the presence of tachycardia was an independent determinant of NT-proBNP elevation ( P  < 0.05) in septic patients, but not in nonseptic patients. Conclusions: Tachycardia was significantly and independently associated with NT-proBNP elevation and lower survival rate in septic patients, although no association was observed in nonseptic patients. Increased NT-proBNP in sepsis with tachycardia might predict poor outcomes in ICU. Abstract : Supplemental Digital Content is available in the text